Manfaat Zaitun Ditinjau dari Sudut Pandang Hadis Nabi SAW dan Ilmu Kesehatan - Tanjung, Nurcholish; Anwar, Husnel (UIN Sumatera Utara Medan, 2024)
In the Qur'an and hadith there is a recommendation to consume olives. The Prophet talked about the advice to maintain health and the need to maintain health for human life. One of them is the hadith narrated by Ibn Majah Number 3320 which discusses the advice of the Prophet to consume olive oil as one of maintaining health. The purpose of this study is to determine the quality of the hadith in Sunan Ibn Majah Nomor 3320, as well as explain the meaning of the hadith about the advice of the Prophet SAW regarding consuming olive oil. This research is library research. To realize this goal, the author collected hadith data by means of takhrij obtained from Sunan Ibn Majah and other supporting books. Furthermore, steps are carried out with the quality of sanad and matan through hadith syarah, sanad and matan criticism, doing i'tibar. The result of this study is that the hadith is of hasan li zhatihi quality, because in the hadith there is a sanad that is assessed kazhib, based on some data. The meaning of the hadith studied as it sounds is the recommendation to use olive oil with a medical approach in scope that explains consuming and using oil for food that is beneficial for health, among the benefits of reducing cholesterol, treating hair, preventing osteoporosis, preventing diabetes, being able to fight cancer, as a facial moisturizer, as an antioxidant, anti-aging, and lowering blood pressure. Research is also found by many scientists and health experts who prove its efficacy and benefits, one of which was held in Italy proving that those who consume olive oil their blood pressure decreases in the blood with levels of 7 points of tension.